PECULIARITIES OF MORAL AND ETHICAL SPHERES OF A PERSONALITY AMONG MEDICAL WORKERS - Дубровина, Светлана; Воронова, Татьяна; Чепурко, Юлия (SWorldJournal, 2021)
The study results of the moral and ethical spheres of a personality among senior and middle-level medical personnel, physicians and nurses are presented in the article. On the basis of a comparative analysis of life goals, moral self-esteem, value orienta